Analysis of consumer behaviour - Levytska, Olha; Lutsiv, Nataliia (Management and Entrepreneurship: Trends of Development, 2025)
The article analyzes the modern approach to the analysis of consumer behavior in circumstances of martial law. The purpose of this work is to substantiate the proposed adaptive approach to analyzing consumer behavior in modern conditions of martial law, economic crisis, and frequent environmental changes. It is determined that despite the relevance of the methods of consumer behavior analysis in modern economic theory (microeconomic, psychological and sociological), they are of a theoretical and descriptive nature and do not allow to assess the impact of changes in various factors on the final volume of consumption. An own approach to the analysis of consumer behavior in circumstances of martial law, which is accompanied by an economic crisis and frequent changes in the environment, is proposed. In conditions of constant change, the behavior of a modern consumer must be adaptive to the environment, which will provide him with a high level of flexibility in meeting his needs. The concept of “internal” and “external” adaptation of a modern consumer is proposed, which is an important condition for his adaptation to frequent changes in the market situation. The unprofitable and profitable state of the consumer is considered, as well as the possibility of forecasting sales volumes for the consumer and for the manufacturer is analyzed in order to ensure his stable position in the market. An economic and mathematical sensitivity method is proposed, which will allow not only to predict the optimal volume of consumption of certain goods for the producer and the consumer, but also with the help of this method it is possible to analyze the impact of changes in the main parameters (prices, fixed costs, etc.) on the volume of consumption. This will greatly facilitate both the producer and the consumer in solving the problem of optimal choice of goods, and will also provide an opportunity to substantiate the reasons that lead to the absence of purchases in different periods of time. The article also proposes a methodology for assessing the level of flexibility of the modern consumer, as well as analyzes the main factors that influence his consumer behavior. We believe that the proposed adaptive approach to analyze consumer behavior in modern conditions of frequent changes will significantly increase the effectiveness of consumer behavior and provide more stable consumption conditions in circumstances of war, economic crisis, and constant market changes. Prospects for further research may include a comprehensive analysis of consumer behavior in changing conditions, which involves assessing market capacity. JEL Classification: L19, M31